Pengelolaan Ruang Bawah Tanah Dalam Reformasi Hukum Pertanahan Di Indonesia - Nur Nafa Maulida Atlanta; Bayu Dwi Anggono; Fendi Setyawan (Ridwan Institute, 2022)
The difficulty of obtaining or using the earth's surface in urban areas has resulted in people starting to look for a number of plots of land below the earth's surface. Thus, a development breakthrough innovation is needed that can address the development of community needs, namely the space below the earth's surface. The use of basements, namely UUPA, automatically refers to property rights in discussing the use of basements. The aim is to find a system for granting land rights or management rights to basements in Law Number 5 of 1960 concerning Basic Agrarian Regulations and Law Number 11 of 2022 concerning Job Creation for individuals. This research is a normative juridical research with collection techniques from the literature which consists of primary and secondary legal materials. The results of this study are the system of granting land rights or management rights to basements in the BAL by basing it on the provisions of Article 2 paragraph (2) of the BAL, the term